REGIONAL PUBLIC SERVICE AGENCY (BLUD) FINANCIAL MANAGEMENT AT PUSKESMAS KARANGREJA, PURBALINGGA DISTRICT - Sugiyarti Sugiyarti; Ambari Ambari; Emiraldo Win Pazqara (DYNAMICS: Journal of Public Administration, 2022)
This thesis is titled: "Financial Management of Regional Public Service Agency (BLUD) in Karangreja Health Center, Purbalingga Regency". The purpose of this research is to describe and explain about the Financial Management of the Regional Public Service Agency (BLUD) at the Karangreja Health Center, Purbalingga Regency. Descriptive qualitative research type. Determination of informants using purposive sampling techniques. Data Analysis uses interactive analytics. The results of the study can be concluded: (1) Aspects of Planning: based on the Plan that has been prepared by the Puskesmas Level Planning Team by applying the principles of accountability governance that has been carried out well. (2) Organizing Aspects: mapping SDMK using the Workload Analysis method (ABK Kes) both at managerial and service level, fulfillment of personal qualifications, human resource development has been well done. (3) Aspects of Direction and Mobilization: guided by the DPA which has been ratified by the PPKD with a detailed distribution of implementation time made monthly by the program holder. (4) Aspects of Supervision: supervision shall be conducted internally or externally including administrative aspects, resources, achievement of program performance, and technical services and if there is found to be a discrepancy in coaching in accordance with the applicable provisions and corrective actions. The financial income of the Karangreja Health Center needs to be improved by: (1) Diversifying the business through cooperation with third parties (parking area management) and forming new business units such as homecare services, psychologist consulting services. (2) Comparative studies to optimize financial blud management. (3) Marketing of existing services through efforts to distribute leaflets, brochures and other promotional media in optimizing services to the community .